The SOPHIE search for northern extrasolar planets: XII. Three giant planets suitable for astrometric mass determination with Gaia - Rey, J. (2017)
We present new radial velocity measurements for three low-metallicity solar-like stars observed with the SOPHIE spectrograph and its predecessor ELODIE, both installed at the 193 cm telescope of the Haute-Provence Observatory, allowing the detection and characterization of three new giant extrasolar planets in intermediate periods of 1.7 to 3.7 yr. All three stars, HD 17674, HD 42012 and HD 29021 present single giant planetary companions with minimum masses between 0.9 and 2.5 MJup. The range of periods and masses of these companions, along with the distance of their host stars, make them good targets to look for astrometric signals over the lifetime of the new astrometry satellite Gaia. We discuss the preliminary astrometric solutions obtained from the first Gaia data release.